Teaching Vocabulary At SD N 01 Jatikuwung GondangrejoKaranganyar In 2013/2014 Academic Year - Muslimah, Isnaini, Mauly Halwat H, M. Hum,.Ph.D, Aryati Prasetyarini, S.Pd, M.Pd (2016)
Vocabulary is an element in teaching English in Elementary School. It is a basic skill that students need to enable them to master four language skills: reading, writing, listening, and speaking. Teaching English vocabulary is important to know the meaning of a word. The purpose of this research is describing the process of teaching learning vocabulary at SD 01 Jatikuwung Gondangrejo Karanganyar. It is conducted to describe the process, the problem faced by the teacher, and the problem solution made by the teacher at SD 01 Jatikuwung Gondangrejo Karanganyar. The type of this research is descriptive research. The writer gets the data of this research from observation, interview and document. The documentare the teaching material, students worksheet and the books used in the class in teaching vocabulary in SD 01 Jatikuwung Gondangrejo. The subject of this research limits to the teacher and students of the fourth grade of SD N 1 Jatikuwung Gondangrejo Karanganyar. The object of this research focuses on the procedure of teaching vocabulary. The data of this research are field notes, students worksheet, interview transcript about teaching vocabulary. The data sources are event, informant, and document. The methods of collecting data there are observation, interview and documentation. In analyzing the data, the writer takes the procedure of reducing the data, displaying the data and drawing conclusion. The result of this research of teaching learning vocabulary show that to attract the students to be enthusiastic in participating in learning English the teacher must use learning media to enable students to follow the spirit of learning, such as pictures, games and other games in order to make the students exited. In the teaching-learning process, the teacher should provide motivation, encouragement to make students interested in the subject learning English.